Purification and Characterization of Thermotoga maritima Endonuclease IV, a Thermostable Apurinic/Apyrimidinic Endonuclease and 3′-Repair Diesterase - Haas, Brian J. (American Society for Microbiology, 1999)
An endonuclease IV homolog was identified as the product of a conceptual open reading frame in the genome of the hyperthermophilic bacterium Thermotoga maritima. The T. maritima endonuclease IV gene encodes a 287-amino-acid protein with 32% sequence identity to Escherichia coli endonuclease IV. The gene was cloned, and the expressed protein was purified and shown to have enzymatic activities that are characteristic of the endonuclease IV family of DNA repair enzymes, including apurinic/apyrimidinic endonuclease activity and repair activities on 3′-phosphates, 3′-phosphoglycolates, and 3′-trans-4-hydroxy-2-pentenal-5-phosphates. The T. maritima enzyme exhibits enzyme activity at both low and high temperatures. Circular dichroism spectroscopy indicates that T. maritima endonuclease IV has secondary structure similar to that of E. coli endonuclease IV and that the T. maritima endonuclease IV structure is more stable than E. coli endonuclease IV by almost 20°C, beginning to rapidly denature only at temperatures approaching 90°C. The presence of this enzyme, which is part of the DNA base excision repair pathway, suggests that thermophiles use a mechanism similar to that used by mesophiles to deal with the large number of abasic sites that arise in their chromosomes due to the increased rates of DNA damage at elevated temperatures.